Log Analyzer for Operational Data Monitoring and Visualization - Apipah Yulia Marsis; Widi Hastomo (Jurnal Ragam Pengabdian, 2026)
Monitoring and visualization of operational data play a crucial role in supporting data-driven system management. A common challenge encountered is that log data from various systems are not integrated into a single central repository, which then impedes monitoring efforts. This study outlined the use of a log analyzer tool to facilitate the monitoring and visualization of operational data through an integrated dashboard. The applied methodology includes log data acquisition, data transformation into a structured database schema, and information representation in a visual format. The developed system provided the capability to observe real-time operational conditions and system performance metrics. Research findings indicate that the implementation of a log analyzer contributed to improved data understanding and increased monitoring process effectiveness. Overall, the results of this study conclude that log analyzer can be a supporting tool in the process of data-driven decision-making in the operational environment of an institution.